Peirce on Reality, Truth, and the Convergence of Inquiry in the Limit - FARBER, Ilya (Institutional Knowledge at Singapore Management University, 2005)
The article analyzes how American philosopher Charles Peirce understands the concept of reality. He identifies the real as that which is independent of what any individual thinks about it and as a type of cognition and as the object of inquiry. Obtrusive realism and projective realism are the two central elements in Peirce's thoughts on reality. A set of problems relating to Peirce's assumption that inquiry must ultimately focus on true beliefs about reality is also presented.